PENGARUH MENYUSUI EKSLUSIF DENGAN STUNTING PADA BALITA 6-59 BULAN: KAJIAN SISTEMATIS - Julianti, Rita; Djuwita, Ratna; Indaryono, Cleo Syahana (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
Stunting is caused by interaction of various complex factors, including breastfeeding practice. Exclusive breastfeeding for the first 6 months was found to be effective in maintaining optimal growth in infants. However, previous studies have shown controversial results regarding the benefits of breastfeeding for stunting prevention. Thus, this systematic review aims to determine the effect of exclusive breastfeeding on stunting prevention in toddlers age 6-59 months in Indonesia. Literature search was carried out systematically based on PRISMA guidelines in international databases such as Embase, PubMed, Sage, Scopus, and ProQuest. Study quality was assessed using the Newcastle Ottawa Scale for cohort and case control studies, while the Joanna Briggs Institute criteria were used to assess cross-sectional studies. 17 studies were found to meet the criteria and presented qualitatively. Seven studies showed significant increase in stunting incidence in children not exclusively breastfed. The relationship between exclusive breastfeeding and stunting is influenced by other factors such as economic level, mother's occupation, maternal malnutrition, low birth weight, low birth length, and intrauterine growth restriction. Exclusive breastfeeding a determinant that has the potential to reduce the incidence of stunting in children under 5 years. Stunting prevention strategies can aim to educate and increase public awareness about the importance of exclusive breastfeeding. Nonetheless, stunting is related to various complex factors, so systemic changes to social, economic, cultural, and maternal factors must still be pursued.